Postharvest handling of temperate fruits in the highland of northern Thailand - Boonyakiat,D. (International Society for Horticultural Science, 2015)
Some temperate fruits such as strawberry, peach, Asian pear, persimmon, Japanese apricot and Asian plum are being grown in the highland of northern Thailand. The Royal Project Foundation is a charitable organization whose mission is to develop a productive agricultural system in the mountainous area of northern Thailand. The project handles these temperate fruits grown in tropical countries. Postharvest handling of these produces is conducted after growers harvest their own fruits mainly by hand. While most fruits, such as strawberry and peach, are graded and packed in selected suitable containers by the growers, some fruits like persimmon and plum are packed by workers at the Development Center Packing House. These fruits are primarily analyzed for chemical residues at the development center before being transported to the Collection Center in Chiang Mai. The Development Center staff checks for both fruit quality and quantity and then loads the fruits onto a truck. At Chiang Mai Collection Center, these fruits are reinspected to meet both quality and quantity standard. They are also randomly checked for chemical residues as well. A certain level of final regrading takes place at the Collection Center. Most persimmons are treated by CO2 to remove their astringency and packed into consumer packages at the Collection Center. For Chiang Mai market places, these fruits are distributed in late afternoon and early the next morning. For Bangkok these fruits are loaded onto refrigerated trucks. The trucks leave Chiang Mai in the evening and then arrive in Bangkok the next morning. Upon arrival in Bangkok, these fruits are inspected again for quality prior to distribution to the market places.